Model Kolaborasi Kebijakan Deradikalisasi Agama Berbasis Pondok Pesantren - Maulana Mukhlis; Syarief Makhya (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Indonesia is facing two strategic issues concerning religion and its relation to Pancasila as the state ideology; radicalism in the name of religion (Islam) and Islamism movement to replace state ideology with caliphate. In response, the government uses hard power (repressive approach) and soft power (preventive efforts) through de-radicalization policy. However, it has not been able to eliminate radicalism threat yet because of lack of civil society involvement. This article offers a collaboration model to make de-radicalization policy to be more optimal to implement so that these would no longer be a serious issue in Indonesia. Pesantren with salafiyyah-aswaja typology is positioned to be a subject because of its great influence on government policy. The design of this study was a descriptive qualitative research in which the data were collected through interviews and observations in five big pesantrens in Lampung province. The result showed that the relationships between government and pesantrens tends to be constructive pattern which in turn pesantrens are not well developed and the determining aspects of collaboration are not fully identified. The core of this model is that the collaboration success in a policy is influenced by some factors such as good initial condition, consultative institution design, leadership facilitation, mutually actors’ preferences, and policy contents that are substantially well understood by collaborators